2006
DOI: 10.1111/j.1365-2214.2006.00678.x
|View full text |Cite
|
Sign up to set email alerts
|

Problems in the coupling of eye and hand in the sequential movements of children with Developmental Coordination Disorder

Abstract: In contrast to skilled adults, both groups of children preferred to foveate the target prior to initiating a hand movement if time allowed. The TD children, however, were more able to reduce this foveation period and shift towards a feedforward mode of control for hand movements. The children with DCD persevered with a look-then-move strategy, which led to an increase in error. For the group of DCD children in this study, there was no evidence of a problem in speed or accuracy of simple movements, but there wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
49
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 21 publications
7
49
0
Order By: Relevance
“…This accords with earlier research showing that mid-aged and older children with DCD can complete simple goal-directed reaching within a comparable timeframe as typically developing children of the same age, at least where the need for online adjustments is minimal (Wilmut, Wann, & Brown, 2006;. What our data suggests is that younger children with DCD may be slower to implement even simple movements within peripersonal space.…”
Section: Chronometric Performance Measuressupporting
confidence: 80%
“…This accords with earlier research showing that mid-aged and older children with DCD can complete simple goal-directed reaching within a comparable timeframe as typically developing children of the same age, at least where the need for online adjustments is minimal (Wilmut, Wann, & Brown, 2006;. What our data suggests is that younger children with DCD may be slower to implement even simple movements within peripersonal space.…”
Section: Chronometric Performance Measuressupporting
confidence: 80%
“…For example, children with developmental coordination disorder (DCD), a disorder of movement that impacts around 5% of children, are less accurate when performing motor imagery tasks and do not show the same level of correspondence between real and imagined movements as their peers without motor impairment (Deconinck, Spitaels, Fias, & Lenoir, 2009;Katschmarsky, Cairney, Maruff, Wilson, & Currie, 2001;Maruff, Wilson, Trebilcock, & Currie, 1999;Williams, Thomas, Maruff, Butson, & Wilson, 2006;Williams, Thomas, Maruff, & Wilson, 2008;Wilson et al, 2004;Wilson, Maruff, Ives, & Currie, 2001). Importantly, these children also demonstrate a pattern of performance on tests of online control consistent with a specific deficit in the in-flight correction of reaching (Hyde & Wilson, 2011a, 2011bWilmut, Wann, & Brown, 2006). Specifically, when completing the DSRT they are slower and less accurate when correcting their movement following unexpected target perturbation compared to their same-age peers, yet are able to perform simple non-jump movements with similar proficiency to controls (Hyde & Wilson, 2011a, 2011b.…”
Section: Patients With a Reduced Ability To Represent Movement Internmentioning
confidence: 92%
“…These data are consistent with other studies that have found similar problems with the feedforward aspect of motor control in DCD. 6,7 The children with DCD attempted to adopt strategies that decreased the problems they experienced, especially when pointing. The most extreme strategy was shown by the two females with DCD, who both walked the chair around to the targets.…”
Section: Discussionmentioning
confidence: 99%
“…One suggestion is that children with DCD may have a problem with preprogramming movements, which may account for slower ⁄ more variable movement times and 'time to peak speeds' (TPS) compared with typically developing children. 6,7 The time from movement onset until TPS is generally accepted to index the part of a movement under preprogrammed, feedforward control. The time from TPS until movement offset (deceleration time) is when the movement comes under feedback control (generally visual).…”
mentioning
confidence: 99%